2017
DOI: 10.1002/app.45807
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanical properties of heat‐polymerized acrylic resin with silver nanoparticles added at different concentrations and sizes

Abstract: The aim of this study was to investigate the effect of silver nanoparticles (AgNPs) incorporation on the flexural strength (FS) of poly(methyl methacrylate) (PMMA). PMMA specimens (65 mm 3 10 mm 3 3.3 mm for flexural test, 50 mm 3 6 mm 3 4 mm for impact test) containing different sizes (40, 50, 60 nm) and concentrations (0.05%, 0.2%) of AgNPs were prepared, along with a control group with no AgNP. Impact strength (IS) and FS of all specimens were measured, and one-way ANOVA and Tukey-Kramer post hoc multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
(47 reference statements)
0
9
0
3
Order By: Relevance
“…% of AgNPs. The 40 nm particles did not affect the mechanical parameters of these composites [ 53 ]. The findings proved that the mechanical properties of the otoimplant did not change after the incorporation of AgNPs even after the 12-month incubation.…”
Section: Resultsmentioning
confidence: 99%
“…% of AgNPs. The 40 nm particles did not affect the mechanical parameters of these composites [ 53 ]. The findings proved that the mechanical properties of the otoimplant did not change after the incorporation of AgNPs even after the 12-month incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Fractures in the dentures usually result from different types of forces like flexural, fatigue, and impact forces. [ 10 11 12 13 14 15 16 ] Beyli and von Fraunhofer[ 12 ] in the year 1980 conducted a study to analyze the causes of fracture of acrylic resin dentures and found that midline fractures in dentures are a flexural fatigue failure. In a similar previous study, Smith DC,[ 10 ] also, concluded midline fractures as a type of fatigue fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 20 23 30 33 34 ] Recently, more attention has been directed toward the incorporation of nanoparticles into PMMA-based denture base material to improve its properties. [ 4 6 16 19 27 35 36 37 38 39 40 41 42 43 ] Oyar et al . [ 16 ] conducted a study to compare the mechanical properties of heat-polymerized PMMA resin with AgNPs added at different concentrations and sizes, while concluding that the properties of the resultant material depend upon the type of the incorporated nanoparticles, their size, shape, and the concentration and interaction of the particles with the polymer matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports investigated dental materials reinforced using micrometer-and nanometer-size materials to create a new composite with enhanced physical and mechanical characteristics [10]. Numerous nanomaterials, such as silver nanoparticles [11], silicon dioxide (SiO2) [12], platinum nanoparticles [13], carbon nanotubes [14], and hybrid nanomaterials [15], were incorporated with PMMA to develop denture bases with improved physical and mechanical properties. For instance, reinforcing PMMA with multiwalled carbon nanotubes (MWCNT) was shown to improve its mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%